Emphasizing Fish, Fisher, and Sea for the Mission of Christian Churches in the Context of the Marine Ecological Crisis: A Response to the Ten Commandments of Food - Maggang, Elia (Mission studies, 2022)
This article offers a theological response to the Ten Commandments of Food (TCF) in the context of the marine ecological crisis. The TCF is a unique and effective campaign for food security which advocates for sustainable living through the mission of Christian churches. As the campaign includes farmers, it reframes food security and sustainability as a part of ecclesial life. However, the neglect of fish, fisher, and sea in the TCF has negative consequences for marine ecosystem. This exclusion endangers the sustainability of marine life and all those who depend on the sea for livelihood and sustenance. Therefore, this article suggests that it is essential to include fish, fisher, and sea in the TCF – noting that they have a crucial place in Christianity as depicted particularly in the ministry of Jesus and his disciples. This will make the TCF a more comprehensive campaign with positive contributions for marine life.